Day 2 Tue, March 27, 2018 2018
DOI: 10.2118/190361-ms
|View full text |Cite
|
Sign up to set email alerts
|

Long Term Thermal Stability of Chemical EOR Surfactants

Abstract: Chemical enhanced oil recovery techniques progressively emerge as a means to increase mature oil fields production. In particular, surfactant flooding allows increasing oil production by lowering the interfacial tension between injection water and crude oil. The effectiveness of surfactants depends on their chemical stability over an extended period of time, which could be impaired by reservoir conditions in terms of temperature, salinity and oxidative conditions. Within the frame of this work, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…The HPLC analyses were performed on an Agilent 1290 Infinity II equipped with a 1260 Infinity II evaporative light scattering detector (ELSD). The ELSD is considered a universal sensor for a variety of surfactants. , The residual surfactant concentration of GS12 after the static adsorption experiments on rock powder was obtained from a calibration curve that correlates the ELSD peak area with known concentrations of GS12. By correlating the GS12 concentration with the initial concentration, it is possible to determine how much GS12 was adsorbed on the rock during the experiment.…”
Section: Methodsmentioning
confidence: 99%
“…The HPLC analyses were performed on an Agilent 1290 Infinity II equipped with a 1260 Infinity II evaporative light scattering detector (ELSD). The ELSD is considered a universal sensor for a variety of surfactants. , The residual surfactant concentration of GS12 after the static adsorption experiments on rock powder was obtained from a calibration curve that correlates the ELSD peak area with known concentrations of GS12. By correlating the GS12 concentration with the initial concentration, it is possible to determine how much GS12 was adsorbed on the rock during the experiment.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, aside from the solubility and compatibility analysis, the thermal stability of the surfactant chemical over a long period of time at reservoir temperature is crucial in designing a stable yet effective natural surfactant for EOR process. Hocine et al [16] reported that in an oxygen free environment, sulfur-based anionic surfactants especially sulfonates remained chemically stable for a duration of 1 year at 100 ˚C temperature. Conversely, [20] in their evaluation of twenty-eight surfactants comprising of the four different types of surfactants, reported that only non-ionic and amphoteric surfactants showed good thermal stability at harsh reservoir conditions.…”
Section: Salinity Scan Analysismentioning
confidence: 99%
“…In addition, Angstadt et al also highlighted the excellent stability of linear alkyl benzenesulfonate for temperatures up to 300 °C during steam injection in low-salinity conditions . Under high-salinity conditions, Hocine et al reported the degradation of sulfates and sulfonates up to 120 °C in months. , Regarding the thermal stability of types of surfactants, the concluding results showed that alkyl benzenesulfonate was superior to olefin sulfonate and petroleum sulfonate, which were more robust to temperature than sulfate surfactants. The degradation mechanism includes the loss of sulfonate or sulfate function by hydrolysis in an acidic or alkaline media, , along with oxidative attacks on the side alkyl chain when exposed to oxygen .…”
Section: Introductionmentioning
confidence: 99%